Windstorm‐induced canopy openings accelerate temperate forest adaptation to global warming. Issue 11 (11th September 2020) - Dietz, Lucie; Collet, Catherine; Dupouey, Jean‐Luc; Lacombe, Eric; Laurent, Lisa; Gégout, Jean‐Claude
Abstract: Aim: Climate change is known to be a driver of changes in forest plant communities and to modify disturbance regimes. We investigated whether forest gaps favoured vegetation adaptation to warmer climates by accelerating the shift of plant communities to a warmer‐adapted composition independently of canopy closure linked to natural forest dynamics. Location: Temperate and mountainous forests of France. Time period: 2002–2018. Major taxa studied: Vascular plants. Methods: Using floristic surveys conducted in 2002 and 2018 in 139 permanent plots set up in unmanaged forest gaps created by windstorms in 1999, we assessed the plant communities' changes in context of global warming. We also compared gap communities to closed communities inventoried in undisturbed forest. A community temperature index (CTI) and a community light index (CLI) were computed for each floristic survey with species temperature optima and Ellenberg light indicator values, respectively. Results: CTI increased significantly in the gaps over the 16 years by 0.11°C/decade on average. During the same period, the CLI decreased, indicating that community thermophilization was not the direct result of an increase in solar radiation linked to gap creation. Models showed that, after canopy recovery, thermophilization was stronger in mountains (+0.54°C) than lowland sites (+0.12°C) compared to undisturbed forests. The difference between former gaps and undisturbed forests resulted from the colonization of warm adapted species and the decline of cold adapted species in gaps. Main conclusions: For a given canopy closure, our results show that thermophilization of understorey communities is higher in areas with previous disturbances than in undisturbed forests. By increasing the speed of thermophilization, the disturbance regime plays a key role in the adaptation of forest communities to climate warming. The effects of large‐scale disturbances on forest plant composition should therefore not be overlooked, especially since disturbance regime tends to intensify with climate change.